Carboplatin and vincristine neurotoxicity in the treatment of pediatric low‐grade gliomas. Issue 11 (16th July 2018) - Rosca, Lorena; Robert‐Boire, Viviane; Delisle, Jean‐François; Samson, Yvan; Perreault, Sébastien
Abstract: Background: Pediatric low‐grade gliomas (LGG) represent 30‐50% of central nervous system pediatric tumors. Over the last decades, the combination of carboplatin and vincristine (CV) has become the first line of treatment in most centers. In a large clinical trial where the efficacy of CV was compared to another regimen, 19% presented grade III neurotoxicity. Despite the fact that CV therapy is widely used for pediatric patients with LGG, no study has reported detailed neurological adverse events and outcome with this treatment regimen. The purpose of this retrospective study is to better understand neurotoxicity associated with CV. Procedure: We conducted a retrospective study to better evaluate the incidence and evolution of neurotoxicity associated with CV in patients with LGG. Results: Twenty‐one pediatric patients were treated with CV at our single institution over 16 years. Most patients had optic glioma. Peripheral neuropathy was present in most patients (86%). Eight patients (38%) had a dose reduction of vincristine due to grade III toxicity (three motor neuropathies, three sensory neuropathies, one constipation, and one dysphagia). Most neurotoxicity occurred during induction or the first maintenance cycle. No ototoxicity was observed during treatment or follow‐up. Conclusions: In our study, neurotoxicity with vincristine occurred two times more frequently than in previously published literature. Careful neurological assessment is important to detect neurotoxicity, especially during induction. The high incidence of neurotoxicity should be considered when selecting a chemotherapy regimen for pediatric LGG.